2016
DOI: 10.1080/15555240.2016.1195693
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organizational support on the life course of trauma in emergency responders from British Columbia

Abstract: Research has consistently demonstrated that following a response to an emergency incident, first responders and first receivers, support staff, and civilian responders are likely to experience trauma. The aim of this article is to explore if the traumatization of emergency responders is influenced by the nature of organizational support toward the psychosocial recovery of staff and volunteers. Twenty-two qualitative inter- views were conducted with emergency responders from British Columbia, Canada. Using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Supervisor support appeared frequently within this review [ 25 , 30 , 31 , 32 , 33 , 43 , 44 , 47 , 50 , 59 , 70 , 71 , 73 , 77 , 80 , 81 , 82 , 88 , 91 , 92 , 98 , 101 , 111 ]. Vaughan et al [ 117 ] highlighted how supervisor support can be improved in PSP organizations by establishing closure for workers, empowering immediate supervisors, and changing the organizational culture. These changes may differ in each organization or discipline but overall, supervisors must consider the needs and long-term mental health status of their workers.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisor support appeared frequently within this review [ 25 , 30 , 31 , 32 , 33 , 43 , 44 , 47 , 50 , 59 , 70 , 71 , 73 , 77 , 80 , 81 , 82 , 88 , 91 , 92 , 98 , 101 , 111 ]. Vaughan et al [ 117 ] highlighted how supervisor support can be improved in PSP organizations by establishing closure for workers, empowering immediate supervisors, and changing the organizational culture. These changes may differ in each organization or discipline but overall, supervisors must consider the needs and long-term mental health status of their workers.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be useful to equip fire department leadership to support the processing of firefighters’ traumatic exposures, in line with empirically supported practices, and to connect exposed firefighters to appropriate services (Vaughan, Moran, Pearce, & Hearty, 2016). Once connected to services, the results of this study may also have implications for clinicians embedded within the fire service.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that support from superiors is particularly influential in buffering against the development of psychopathology (Kleim & Westphal, 2011). Organizational-level support has also been associated with a greater degree of recovery from traumatic stress exposure in one sample of first responders (Vaughan et al, 2016). To this end, organizations that employ SWs may consider incorporating regular check-ins or support sessions among SWs and with supervisors, hiring a therapist to offer professional mental health services to SWs, and creating a work culture that recognizes the impact of trauma and stress on SWs’ lives and provides opportunities for healing and self-care.…”
Section: Discussionmentioning
confidence: 99%